Understanding enterprise SOA - Pulier, Eric.; Taylor, Hugh. (Greenwich, Conn. : Manning ; London : Pearson Education [distributor], 2006)
The book gives technologists and business people an invaluable and until now missing integrated picture of the issues on SOA and their interdependencies. The book draws conclusions from actual experiences of real companies in diverse industries, from manufacturing to genome research. It cuts through vendor hype and shows you what it really takes to get SOA to work. The book reviews core SOA technologies and uncovers the critical human factors involved in deploying them; shows how enterprise SOA changes the terrain of EAI, B2B commerce, business process management, "real time" operations, and enterprise software development in general.
Includes index
oif 08/09/14
Loan
Keywords: Computer software -- Development; Computer architecture; System design; Business -- Data processing